Where currents meet: the offshore interface between corruption, offshore finance centres and economic development. - HAMPTON, Mark P. (1996)
Examines tax havens and offshore finance centres which form an interface between developed countries and LDCs. Argues that these financial channels facilitate and can even encourage onshore corruption.